COMMUNITY PARTNERSHIP STRATEGIES FOR EVENT BUSINESS SUCCESS IN INDONESIA - Setiadi, Nugroho J.; FARHANSYAH, Ihsan T; ILYUS, Antonio; SABIELLA, Imanda D (Bina Nusantara University, 2025)
This study explores the business expansion strategies of 'MELAYA' in Indonesia, with a focus on leveraging community partnerships. Over the past decade, Indonesia's music and events industry has experienced substantial growth, driven by increasing public interest in concerts and festivals. The research aims to analyze how community partnerships can enhance the success of MELAYA's business expansion while addressing the intense competition from established players in the industry. MELAYA, which operates primarily in Bandung's music and event sector, faces challenges in securing partnerships and building brand awareness as it expands into other cities. Optimized digital marketing strategies are expected to foster trust in partnerships and support this expansion. The findings from this research are intended to provide insights into the effectiveness of community partnership strategies in driving event business growth and offer solutions to overcome competitive challenges in this dynamic industry.